Race, real estate, and uneven development : the Kansas City experience, 1900-2010 - Gotham, Kevin Fox. (State University of New York Press, 2014)
"Updated second edition examining how the real estate industry and federal housing policy have facilitated the development of racial residential segregation"--Provided by publisher.